The effect of new e-commerce platform’s OSC promotion on consumer cognition: from cognitive legitimacy and cognitive psychology perspective - Yu, Deng; Wei, Han; Xuefeng, Zhang; Zhongxuan, Huang; Yijun, Zhang (Frontiers in Human Neuroscience, 2024)
In the realm of emerging e-commerce platforms, a potential area of research pertains to the impact of online carnival promotions (OSC) on consumer perceptions. Two studies were undertaken to explore this topic. The first study involved 220 participants in a questionnaire experiment with two groups, focusing on the role of cognitive legitimacy as a mediator in the connection between OSC events organized by new e-commerce platforms and consumer perceptions. The findings indicated that through OSC activities, these platforms could establish cognitive legitimacy, leading to enhanced positive purchase intentions. The second study, involving 33 participants in an event-related potentials (ERPs) experiment, aimed to investigate differences in consumer perceptions resulting from OSC promotions compared to general promotions conducted by new e-commerce platforms. The results demonstrated that exposure to OSC promotion posters led to the elicitation of larger P2 and N2 components in response to the new platform logo, as opposed to general promotions. These outcomes suggest that the implicit memory of distinct promotional activities influences target identification and cognitive control mechanisms in online shopping contexts, potentially impacting explicit consumer behavioral characteristics.